Effect of biostimulants on the fruit quality of Golden Glory apple in Chihuahua, Mexico - Acevedo-Barrera, Angélica; Acevedo-Barrera, Angélica; Gutiérrez-Chávez, Aldo; Pérez-Leal, Ramona; Soto-Parra, Juan; Villa-Martínez, Alejandra; Hernández-Huerta, Jared (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The cultivation of apple (Malus domestica (Borkh.) Borkh.) holds significant global importance due to their flavor and nutritional value. In Mexico, Chihuahua leads in production, yet the response of the Golden Glory variety to biostimulants remains unstudied. This study aimed to evaluate the effect of biostimulants on fruit quality in Golden Glory apple. Conducted in Namiquipa, Chihuahua, during the 2023 season, the study employed randomized experimental design with treatments (amino acids, algae, fulvic acids, and a control) spraying weekly from flowering to near harvest. Fruit characteristics were evaluated 90 days post-initial treatment. Amino acids significantly improve fruit weight (27.98 %), diameters (8.41 % polar and 9.28 % equatorial), color (178.8 %), and total soluble solids (TSS;5.72 %), while reducing malic acid content and enhancing TSS/AT ratio by 23.21 %, with no impact firmness. Fruit quality met marketing standards. Seaweed and fulvic acids treatment showed no significant improvement parameters. These results underscore amino acids ‘efficacy in enhancing 'Golden Glory' apples quality.